2015 Annual IEEE Systems Conference (SysCon) Proceedings 2015
DOI: 10.1109/syscon.2015.7116728
|View full text |Cite
|
Sign up to set email alerts
|

Developing systems thinking among engineers: Recent study findings

Abstract: The current study deals with the development of systems thinking among systems engineers. The goals of the study are to identify the factors that influence the development of systems thinking among systems engineers and to find ways to encourage this development. This study is part of the effort of a full range of studies, which combine different disciplines, are being conducted among a number of populations, and use a variety of research tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Koral et al [21] identified the factors that influence the development of systems thinking among industrial and systems engineers. In this study, contrasted group validity was determined by comparing the grades of two contrasted groups-industrial and systems engineers and particular engineers such as software and hardware engineers.…”
Section: Validating the Tool -Results Of Recent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Koral et al [21] identified the factors that influence the development of systems thinking among industrial and systems engineers. In this study, contrasted group validity was determined by comparing the grades of two contrasted groups-industrial and systems engineers and particular engineers such as software and hardware engineers.…”
Section: Validating the Tool -Results Of Recent Studiesmentioning
confidence: 99%
“…The result of this questionnaire is one of the 16 character archetypes. According to Koral et al [21], 60% of the respondents belong to the STJ (Sensing, Thinking, Judging) group. This finding emphasizes the fact that a large percentage of the engineers belong to particular personality groups with unique traits.…”
Section: Validating the Tool -Results Of Recent Studiesmentioning
confidence: 99%
“…Frank et al [8] define systems thinking as a "major high-order thinking skill that enables individuals' to successfully perform systems engineering tasks" (p. 32) in the development of their Capacity for Engineering Systems Thinking (CEST) instrument. Kordova et al [16] describe systems thinking as a concept that prioritizes understanding of the relationships between components rather than knowledge of the components. These definitions all tie together the common threads of managing interdependence and complex relationships, while describing systems thinking as a skill, valuable for modern professionals.…”
Section: Systems Thinkingmentioning
confidence: 99%
“…Students don't have to worry about designing the individual components and can focus on using a systems approach thinking for solving more complex and realistic problems. A systems approach thinking, unlike the computation thinking, focuses on how all the individual components or elements as a whole act together to form a system that achieves a common goal or purpose [6], [7], and [8]. It provides students with a wider view that involves a larger number of interactions from the individual components to influence the overall performance of the system behavior.…”
Section: Introductionmentioning
confidence: 99%
“…From the research literature one way to develop system thinking is by having students work on practical projects that relates to their studies. In turn, the practical projects provide the opportunity for students to learn about the various characteristics of the system by holding distinct roles within a dynamic group environment [8], and [9]. Both computational and system thinking methods provide complementary frameworks that allow students to decompose a complex design problem into more manageable algorithmic based problems.…”
Section: Introductionmentioning
confidence: 99%